Access regulation and geographic deployment of a new generation infrastructure - David Flacher; Hugues Jennequin (International Telecommunications Society (ITS), 2012)
This article addresses the impact of regulatory policy on levels of infrastructure deployment and derived welfare in the telecommunications sector. The model considers two potentially coexisting and partially competing techniques (the old ADSL - Asymmetric Digital Subscriber Line - technique) - and the new FTTH - Fibre To The Home - one). Competition is supposed to be high on the ADSL market because of already existing regulation. We assume that two types of operators are competing in order to provide FTTH services: those that build and operate the new infrastructures (OPf1) and those that just buy access to them (OPf2). In our model, the level of investment is decided at stage 1 and the access price is decided at stage 2. At stage 3, OPf1 and OPf2 compete à la Cournot. This common framework allows us to show that the regulation defining access price in order to maximise infrastructure deployment is strictly equivalent to the case in which no regulation applies. We also derive from the model that these two types of regulation induce higher social welfare, but lower numbers of FTTH consumers than cost-oriented access regulation. Finally, we show that the level of infrastructure deployment (as well as social welfare and number of FTTH consumers) will be at its highest if both investment and access price decisions are taken by the regulator. This suggests that the social optimum will be achieved through a call-for-tender process including deployment and access prices requirements.
Keywords: L43; L51; L96; R58; 330; Access regulation; geographic deployment; network industries; telecommunications; investment.